2017
DOI: 10.1177/1065912917706549
|View full text |Cite
|
Sign up to set email alerts
|

For Richer or Poorer: The Politics of Redistribution in Bad Economic Times

Abstract: This paper examines the consequences of economic downturns for states’ redistributive politics. We track state policies from 1980 through 2010 and illustrate how economic downturns led states to adopt budget-balancing policies by suppressing both the increased spending on programs benefiting the poor otherwise expected under Democratic Party control and the tax cuts for the wealthy otherwise expected under Republican Party control. We also undertake a natural experiment case study—comparing the forty Democrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…was combined with increased taxes and accompanied by reductions in state and local government employment levels (Campbell and Sances, 2013;Gordon, 2012;Rigby and Hatch, 2017).…”
Section: Social Protection Measures Were Key Components Of the Fiscalmentioning
confidence: 99%
“…was combined with increased taxes and accompanied by reductions in state and local government employment levels (Campbell and Sances, 2013;Gordon, 2012;Rigby and Hatch, 2017).…”
Section: Social Protection Measures Were Key Components Of the Fiscalmentioning
confidence: 99%
“…But, even that was insufficient to offset lost state revenue. In response to budgetary shortfalls, states cut spending, raised taxes, and reduced state and local government employment (Campbell & Sances, ; Gordon, ; Rigby & Hatch, ).…”
Section: Policy Responsesmentioning
confidence: 99%
“…Rigby and Hatch () analyzed state policy choices in response to the GR and observed that in addition to having fewer resources and increased demands from safety net programs, many states were institutionally constrained by balanced budget requirements. But these balanced budget requirements can also be an opportunity for politicians.…”
Section: Policy Responsesmentioning
confidence: 99%
See 2 more Smart Citations